Między minimalizmem a melodramatem. Przestrzeń filmowa w kinie rumuńskiej nowej fali - Domalewski, Adam (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2020)
The starting point for considering the means of creating and designing a film space in Romanian New Wave cinema is the thesis that Romanian film art in the 21st century is an artistic response to the times of communism and that images of the post-socialist architectural space – their multi-faceted functionalization in film mise-en-scéne – are the key method of evoking memories of the past. The article discusses, via the example of movies by Crisitian Mungiu, Corneliu Porumboiu and Cristi Puiu, (1) ways of depicting the “closing” of film characters in the cramped interiors of their apartments and (2) film images of individuals’ alienation in public spaces, both of them allusively referring to the times of the oppressive Nicolae Ceaușescu regime. The most important cinematographic devices used by the authors of the Romanian New Wave cinema include: seemingly static shots, which, however, are filmed with a camera that is constantly gently moving and observing, and tableau shots. A common feature of all the considered works is the panopticism of the film world: the private and public spaces designed in them easily become a place of constant, panoptical observation. In the summary, the author remarks on and briefly discusses the coexistence of the aesthetics of minimalism / realism with the melodramatic elements in the cinematic structure of Romanian New Wave films.